PENDIDIKAN TRANSPORTASI DAN LOGISTIK DALAM MENGHADAPI TANTANGAN GLOBAL - Indriyati Indriyati; Juliater Simarmata (Jurnal Manajemen Bisnis Transportasi dan Logistik, 2017)
Facing  the challenges of Globalization Era and Readiness to enter the era of Asean Economic Community (AEC) Economic Market, Indonesia seems to be in doubt. Due to the availability of experts in the field of Transport and Logistics is still very inadequate, one of the toughest challenges facing the Asean open market is the use of experts in the field of Transport and Logistics. The reason, foreign logistics companies that will open operations in Indonesia will participate scramble to find reliable personnel in the field of Transport and Logistics services nationwide. The need for logistics experts is around 17,000 people per year, to meet a minimum of two logistics experts in every large and medium-sized company engaged in manufacturing, trading, retail and distribution, various industries in need. Therefore, Trisakti responds to the challenges in the business world of Transportation and Logistics in the provision of education to create a curriculum of education of logistics experts who are reliable and globally reputable. That is by realizing Trisakti Institute of Transport and Logistics (ITL).